Q fever vertebral osteomyelitis among adults: a case series and literature review. Issue 4 (3rd April 2021) - Ghanem-Zoubi, Nesrin; Karram, Tony; Kagna, Olga; Merhav, Goni; Keidar, Zohar; Paul, Mical
Abstract: Background: Q fever osteoarticular infections are a rare complication of the chronic form of Q fever. We aimed to characterize chronic Q fever vertebral osteomyelitis through our experience and a review of the literature. Methods: Four adult patients with Q fever vertebral osteomyelitis diagnosed in a tertiary hospital in northern Israel between 2016 to 2020 are described. In addition, a 30 years' literature review of Q fever vertebral osteomyelitis, characterizing predisposing factors, clinical presentation, course of disease, treatment and outcomes, was performed. Results: Thirty-four adult patients with Q fever vertebral osteomyelitis were identified. The vast majority were male (30/34, 88%) with a mean age of 67.2 ± 10 years. Involvement of the adjacent aorta, likely the origin of the infection, was observed in 23/34 (68%) of the patients, usually among patients with aortic graft or aneurysm. Clinical presentation was insidious and fever was frequently absent. Delayed diagnosis for months to years after symptoms onset was frequently reported. Vascular infections were managed with or without extraction of the infected aneurysm/aorta and graft placement. The outcome was variable with limited follow-up data in most cases. Patients were usually treated with prolonged antimicrobial therapy, most commonly doxycycline and hydroxychloroquine combination therapy. Conclusion: Q fever should be included in the differential diagnosis of vertebral osteomyelitis in endemic settings, in particular when concomitant adjacent vascular infection exists.